Comparison of the GEANT4 Releases 8.2 and 9.2 in terms of a pCT Reduced Calibration Curve - Yevseyeva, O.; Assis, J. T. de; Milhoretto, E.; Evseev, I. G.; Schelin, H. R.; Ahmann, F.; Paschuk, S. A.; Setti, J. A. P.; Denyak, V.; Diaz, K. S.; Hormaza, J. M. [UNESP]; Lopes, R. T.; et al. (Ieee, 2010)
The GEANT4 simulations are essential for the development of medical tomography with proton beams - pCT. In the case of thin absorbers the latest releases of GEANT4 generate very similar final spectra which agree well with the results of other popular Monte Carlo codes like TRIM/SRIM, or MCNPX. For thick absorbers, however, the disagreements became evident. In a part, these disagreements are due to the known contradictions in the NIST PSTAR and SRIM reference data. Therefore, it is interesting to compare the GEANT4 results with each other, with experiment, and with diverse code results in a reduced form, which is free from this kind of doubts. In this work such comparison is done within the Reduced Calibration Curve concept elaborated for the proton beam tomography.